Historia social de la formación en enfermería en Santa Marta, Colombia (2023)
Introduction: Founded in 1994, the Nursing Faculty of Universidad Cooperativa de Colombia de Santa Marta became the first experience of formation in nursing in the city. It started within the circumstances generated by the political constitution of 1991, Law 100 of 1993 and Law 266 of 1996 which regulates the practice of nursing profession in Colombia. From the local viewpoint, the formative process implied the recognition and positioning of nursing in the city. Objective: To analyze the historical development of the formative process of nurses in Santa Marta, Colombia. Methods: A historical study combining oral history and documentary review. The oral history was based on semi-structured interviews made with graduates, professors and managerial staff who have worked in the program. For the information analysis, the data was organized, classified and processed, as well as coded and interpreted according to an analysis matrix. Results: In its twenty two years of existence, the formative process of nursing in the city of Santa Marta has used a variety of strategies aimed at positioning the profession in the city and at constructing the nursing discourse, identity and performance. Conclusions: The social history of nursing formation allows visualizing processes of positioning and recognition of profession as well as a series of initiatives that remain hidden in the traditional versions of history. © 2019 Revista Cubana de Enfermería.